OCCUPATIONAL ACCIDENT EYE OF WORKERS NURSING ADMINISTRATION OF ANTINEOPLASTIC CHEMOTHERAPY: A REVIEW LITERATURE (Fiep Bulletin - online, 2011)
This study is intended to describe the trends of publications about occupational eye accidents in nursing personnel in the administration of cancer chemotherapy, the level of circulation of such productions, besides the analysis of the goals proposed by these studies, following the footsteps of an integrative review of literature. Found 164 articles in the Virtual Health Library (VHL) using the keywords "nursing occupational accidents", "health worker", "risks of chemotherapy," "risk eye," eye health nursing, eye health worker ''and "occupational hazards eye" in the databases of the health sciences in general and in specialized areas. After applying the inclusion criteria, we come to the sample of 126 publications. Data collection was conducted between April and June 2009. It was observed that most studies were conducted by doctors nurses, teachers and graduates. We conclude that contribute to the body of nursing knowledge and strengthening the profession by conducting research for these products in addition to the analysis of the goals proposed by these studies, in analyzing its applicability to the care and study of concepts.
Keywords: employees of nursing; occupational accidents eye; risks of chemotherapy; eye health nursing; eye health worker; the risk agent and integrative review